ANALISIS TINGKAT KESEHATAN UNIT SIMPAN PINJAM PADA KOPERASI SERBA USAHA REJOSARI PEKANBARU - Kartikowati, Sri Kartikowati; Haryana, Gani Haryana; ', Nurwahidjah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of the research determine of the health level of Saving-Loan unit within the cooperative of multi bussines Rejosari Pekanbaru. The health level was calculated based on the ACT of cooperative and small bussines Republic Indonesia no: 20/per/KUKM/XI/2008, is was covered capital, asset quality, management, efficiency, liquidity, independence and growth, and the identity of cooperative. The method is kuantitatif approach research where data was collected in the form of five years financial report. The research found that the Saving-Loan unit was in the moderate health level. In detail its healt can be discrabe that in 2010 the cooperative achieved score of 63.65; in 2011 the cooperative achieved score 63.65; in 2012 achieved score 63.65, in 2013 achieved score 64.90; and in 2014 the cooperative achieved score 66.15. As a result the multi bussines Rejosari of thained the range score between 60 â€“ 80 that equal to moderate health level. Keyword: the soundness of the cooperative, capital, asset quality, management, efficiency Â